Experimental results from a four-year targeted education voucher program in the slums of Delhi, India. (December 2019) - Dixon, Pauline; Egalite, Anna J.; Humble, Steve; Wolf, Patrick J.
Highlights: Four years after random assignment, we find large positive impacts of voucher use on test scores in English (0.31σ p < .05). Targeted vouchers programmes in India could provide girls with quality education focusing on English proficiency. Hindi language skills could be obtained more at home or within a community for students from poor backgrounds. The positive impact of the ENABLE program is four times the average impact of an education initiative on pupil test scores. Abstract: We present experimental evidence from a school choice program carried out in a 20-square kilometer, highly urbanized slum area known as Shahdara, which is situated in East Delhi, India. The lottery-based allocation of vouchers allows us to structure an impact evaluation as a randomized controlled trial. We conduct an Intent-to-Treat (ITT) analysis of the impact of the offer of a voucher as well as a Treatment-on-Treated (TOT) analysis of the impact of using a voucher, employing the lottery results as an instrumental variable. Four years after random assignment, we find large positive impacts of voucher use on student test scores in English (0.31σ, p < .05). We find suggestive negative impacts of voucher use on test scores in the native language of Hindi (−0.20σ, p < .10), but this impact is not significant at the standard 95% confidence level. We find no voucher impact on student test scores in mathematics.